Distributary channels in the fluvial to tidal transition zone. Issue 3 (28th March 2017) - Kästner, K.; Hoitink, A. J. F.; Vermeulen, B.; Geertsema, T. J.; Ningsih, N. S.
Abstract : Coastal lowland plains under mixed fluvial‐tidal influence may form complex, composite channel networks, where distributaries blend the characteristics of mouth bar channels, avulsion channels, and tidal creeks. The Kapuas coastal plain exemplifies such a coastal plain, where several narrow distributaries branch off the Kapuas River at highly asymmetric bifurcations. A comprehensive geomorphological analysis shows that trends in the channel geometry of all Kapuas distributaries are similar. They consist of a short, converging reach near the sea and a nonconverging reach upstream. The two parts are separated by a clear break in scaling of geometrical properties. Such a break in scaling was previously established in the Mahakam Delta, which suggests that this may be a general characteristic in the fluvial to tidal transition zone. In contrast to the geometrical trend similarities, a clear difference in bed material between the main and side distributaries is found. In the main distributary, a continuous trend of downstream fining is established, similar to what is often found in lowland rivers. In the side distributaries, bed material coarsens in the downstream direction. This indicates an undersupply of sediment to the side distributaries, which may contribute to their long‐term stability as established from historical maps. Tides may be the main agent preventing fine sediment to settle, promoting residual transport of fine material to the coastal ocean. Key Points: Channel geometry trend breaks in the tidal‐fluvial transition zone Trends in channel geometry differ from those in bed material grain size Channel properties in the Kapuashave a mixed character